Allometric model to estimate biomass and carbon of seedling in Pangarengan mangrove forest, Cirebon, West Java - Budi Mulyana; Ris Hadi Purwanto; Puspita Intan Sari; Afni Atika Marpaung; Muhamad Faqih Hidayatullah; Ilham Satria Raditya Putra; Agik Dwika Putra; Rina Reorita (Jurnal GALAM, 2021)
The mangrove ecosystem in Pangarengan Village, Cirebon District, provides benefits for environmental services, including as carbon sinks and stores. In estimating the carbon storage of mangrove forests, in general, allometric equations are used. Unfortunately, the allometric equations currently available are still composed of the stages of growth of saplings, poles, and trees. Thus, the purpose of this study was to develop an allometric model for seedlings in mangrove forests. The research was conducted in June 2021 in the mangrove forest of Pangarengan Village, Cirebon District. The equipment that used in the study were calipers, measuring tape, digital scales, and crop shears. Research materials were mangrove seedlings of Rhizophora mucronata, Avicennia marina, and Sonneratia caseolaris. The best allometric model in estimating dried weight biomass with base diameter predictor is Y = 35,013 Dp1,860 (R2adj = 0,873; SEE = 0,472) using tip diameter predictor is Y = 249.573 Du2,276 (R2adj = 0,524; SEE = 0,710). While the allometrics for estimating the carbon content of seedlings were Y = 5,835 Dp1,804 (R2adj = 0,831; SEE = 0,528) and Y = 35,750 Du2,107 (R2adj = 0,607; SEE = 0,805). Thus, the power allometric model with base diameter predictor was quite good in estimating dried weight biomass and seedling carbon content in the mangrove forest of Pangarengan Village.